2017
DOI: 10.1021/acs.molpharmaceut.7b00826
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Mucosal Immune Response of Newcastle Disease Virus DNA Vaccine Using N-2-Hydroxypropyl Trimethylammonium Chloride Chitosan and N,O-Carboxymethyl Chitosan Nanoparticles as Delivery Carrier

Abstract: Because mucosal sites are the entry ports of pathogens, immunization via mucosal routes can extremely enhance the immunity. To elevate the potential of N-2-hydroxypropyl trimethylammonium chloride chitosan (N-2-HACC) and N,O-carboxymethyl chitosan (CMC) nanoparticles as a mucosal immune delivery carrier for DNA vaccines, we prepared the NDV F gene plasmid DNA with C3d6 molecular adjuvant (pVAX I-F(o)-C3d6) encapsulated in the N-2-HACC-CMC nanoparticles (N-2-HACC-CMC/pFDNA-C3d6 NPs). The N-2-HACC-CMC/pFDNA-C3d6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 51 publications
0
35
0
1
Order By: Relevance
“…Our group developed the plasmid DNA of NDV F gene encapsulated in the N-2-HACC/CMCS nanoparticles, and found that intranasally immunized chickens with the nanoparticles produced higher anti-NDV IgG and sIgA antibody than the chickens in other groups did. They also had significantly stimulated lymphocyte proliferation and higher levels of induced IL-2, IL-4 and IFN-levels, which demonstrated that the nanoparticles could serve as efficient DNA delivery systems and vaccine adjuvants for stimulating humoral, cellular, and mucosal immune [58].…”
Section: Nucleic Acids Encapsulated Into Polymer-based Nanoparticlesmentioning
confidence: 93%
“…Our group developed the plasmid DNA of NDV F gene encapsulated in the N-2-HACC/CMCS nanoparticles, and found that intranasally immunized chickens with the nanoparticles produced higher anti-NDV IgG and sIgA antibody than the chickens in other groups did. They also had significantly stimulated lymphocyte proliferation and higher levels of induced IL-2, IL-4 and IFN-levels, which demonstrated that the nanoparticles could serve as efficient DNA delivery systems and vaccine adjuvants for stimulating humoral, cellular, and mucosal immune [58].…”
Section: Nucleic Acids Encapsulated Into Polymer-based Nanoparticlesmentioning
confidence: 93%
“…More so, when administered without any delivery vehicle, they are easily degraded by the nucleases before they reach their final destination. Nonetheless, the use of adjuvants and delivery vehicle may overcome some of these limitations [ 142 , 143 ].…”
Section: Vaccination Strategiesmentioning
confidence: 99%
“…) and DNA vaccine (Zhao et al . ) have been studied. In particular, the DNA vaccine, named ‘the third‐generation vaccine’, has attracted increased interest recently because of its easy manipulation and stability for transportation (Heppell and Davis ).…”
Section: Introductionmentioning
confidence: 99%
“…Although vaccination is the best way to prevent ND, vaccine failure in providing protection against genotype VII ND has been reported (Ji et al 2018). In addition to the traditional inactivated vaccine, vaccine candidates such as the reverse genetics vaccine (Kim and Samal 2018), subunit vaccine (Kang et al 2016) and DNA vaccine (Zhao et al 2018) have been studied. In particular, the DNA vaccine, named 'the third-generation vaccine', has attracted increased interest recently because of its easy manipulation and stability for transportation (Heppell and Davis 2000).…”
Section: Introductionmentioning
confidence: 99%